Modified silicon-carbon composite material as well as preparation method and application thereof

Through the preparation method of modified silicon carbon composite materials, the structure layer of lithium fluoride particles and carbon inlay solves the problem of unstable problem of silicon electrode material SEI membrane in lithium -ion battery, which significantly improves the electrochemical performance of the battery.

CN119381422AInactive Publication Date: 2025-01-28CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202411325705.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In lithium-ion batteries, silicon electrode materials form an unstable solid electrolyte interface (SEI) film during charging and discharging, resulting in problems such as incomplete deintercalation of lithium ions, poor conductivity, poor cycle stability and low magnification.

Method used

The preparation method of modified silicon carbon composite material is used to mix silx carbon composite materials with fluoride and perform heat treatment, pickling and drying under the protection of inert gas to form a carbon fluoride inlaid structure with fluoride. Cover the surface of the silicon particles to form a structural layer of fluoride particles and carbon inlay.

Benefits of technology

This modified material can significantly improve the rapid transmission capacity of electronic ions, enhance mechanical strength, reduce the risk of fracture, and increase conductivity, thereby improving the electrochemical properties of lithium -ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381422A_ABST
    Figure CN119381422A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery materials, and particularly provides a modified silicon-carbon composite material and a preparation method and application thereof.The modified silicon-carbon composite material with silicon particles coated with a carbon layer as an improvement basis is subjected to heat treatment, acid pickling and drying on a mixture of the silicon-carbon composite material and fluoride under protection of inert gas, and the modified silicon-carbon composite material is obtained. According to the modified silicon-carbon composite material, a fluorocarbon mosaic structure with carbon fluoride defects is formed outside silicon particles, the modified material is assembled into a lithium ion battery, after charging and discharging are conducted, fluorocarbon bonds are broken, fluorine-lithium bonds are generated, and a lithium fluoride particle and carbon mosaic structure layer is formed outside the silicon particles in a coating mode. The single-layer structure formed outside the silicon particles can effectively improve the rapid transmission capacity of electrons and ions, has excellent mechanical strength and better fracture resistance in the continuous charging and discharging process, and further improves the conductivity, so that the electrochemical performance of the lithium ion battery is remarkably improved, and the preparation method is simple and convenient to control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to a modified silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] Lead-acid batteries used in traditional fuel vehicles have the problem of irreversible sulfate formation during discharge, which is not enough for the next generation of all-electric and hybrid vehicles. Since the commercialization of lithium-ion batteries in 1990, they are expected to replace lead-based system batteries due to their high energy density and long service life. Carbon is one of the main materials used in lithium secondary batteries and hybrid lithium-ion capacitors (LICs). The carbon-based negative electrode stores lithium between graphite sheets through an intercalation mechanism. Traditional lithium-ion batteries are composed of graphite negative electrodes and metal oxide positive electrodes. However, the theoretical specific capacity of graphite negative electrodes is low and cannot meet people's growing demand for high energy density.

[0003] The silicon negative electrode based on alloy reaction has high specific capacity (3579mAh g-1, Li3.75Si) and low lithium insertion potential (0.3V to Li+ / Li), and has no dendrite problem, which is an important negative electrode choice for building lithium batteries. However, the huge volume expansion of silicon (>300%) leads to the intensification of the side reaction between the electrolyte and silicon; moreover, the dehydrofluorination of FEC caused by Lewis acid PF5 produces corrosive hydrofluoric acid (HF), which causes damage to the electrode material and the electrode interface, accelerating the failure of the negative electrode. The current optimization of silicon negative electrode mainly focuses on silicon nano-sizing strategy, silicon-carbon composite structural materials, binder design and electrolyte optimization strategy. However, silicon will continuously expand and shrink during the continuous charging and discharging process, and the solid electrolyte interface (SEI) film on the silicon surface will break and re-form with the volume expansion, making the SEI film thicker and thicker. Since the formation of Sel film consumes lithium ions, it causes a large irreversible capacity. At the same time, the poor conductivity of the SEI film will also cause the impedance of the electrode to increase continuously during the charge and discharge process, hindering the electrical contact between the current collector and the active material, increasing the diffusion distance of lithium ions, hindering the smooth deintercalation of lithium ions, and causing rapid capacity decay. At the same time, the thicker SEI will also cause greater mechanical stress, causing further damage to the electrode structure. The unstable SEI layer will also cause silicon and silicon-lithium alloys to be directly in contact with the electrolyte and lose capacity.

[0004] In order to solve the problem of unstable SEI layer on the surface of silicon negative electrode, researchers have tried a variety of modification strategies, among which the construction of artificial solid electrolyte interface layer is one of the effective means. The construction of artificial SEI film can effectively inhibit the formation of natural SEI film and solve the problem of incomplete lithium ion deintercalation in silicon-based negative electrode. However, it is still difficult to construct in situ an SEI layer with high ionic and electronic conductivity, high mechanical strength, and the ability to adapt to the volume expansion problem during silicon lithiation and delithiation. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the SEI film formed by the silicon electrode material in the prior art during the continuous charge and discharge process will continue to break and form, hindering the ion extraction and causing the conductivity to deteriorate, thereby resulting in poor cycle stability and low rate of lithium ion batteries. A modified silicon-carbon composite material and its preparation method and application are provided.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0008] Step 1, mixing the silicon-carbon composite material and the fluoride;

[0009] Step 2: heat-treating the mixture obtained in step 1 in a tube furnace under the protection of inert gas;

[0010] Step 3, pickling and drying the material after the heat treatment in step 2 to obtain a modified silicon-carbon composite material;

[0011] The structure of the silicon-carbon composite material is that the surface of silicon particles is coated with a carbon layer.

[0012] The invention provides a method for preparing a modified silicon-carbon composite material. The silicon-carbon composite material in which silicon particles are coated with a carbon layer is used as an improved basis. A mixture of the silicon-carbon composite material and a fluoride is subjected to heat treatment, pickling and drying under the protection of an inert gas to obtain the modified silicon-carbon composite material. The modified material forms a carbon-fluorine embedded structure with fluorinated carbon defects on the outside of the silicon particles. The modified material is assembled into a lithium-ion battery. After charging and discharging, the carbon-fluorine bonds are broken and fluorine-lithium bonds are generated. The silicon particles are coated with lithium fluoride particles and a carbon-embedded structural layer. The single-layer structure formed on the outside of the silicon particles can effectively improve the rapid transmission capability of electrons and ions, and has excellent mechanical strength, better fracture resistance during continuous charging and discharging, and further improved conductivity, so that the electrochemical performance of the lithium-ion battery is significantly improved.

[0013] Furthermore, the fluoride is at least one of sodium fluoride, cobalt fluoride and magnesium fluoride.

[0014] Furthermore, in step 1, the weight ratio of the silicon-carbon composite material to the fluoride is 1 to 5:1. Studies have found that the addition ratio of the silicon-carbon composite material and the fluoride is an important factor affecting the electrochemical performance of the modified composite material. If the addition ratio of the two is too low or too high, the improvement of the electrochemical performance will be affected. Preferably, in step 1, the weight ratio of the silicon-carbon composite material to the fluoride is 2 to 4:1. For example, 2:1, 3:1, 4:1.

[0015] Furthermore, in step 2, the heat treatment temperature is 200-600°C; and / or, the heat treatment time is 2-8h. Studies have found that too low a heat treatment temperature may result in poor carbon-fluorine mosaic structure effect, and too high a heat treatment temperature may reduce the mechanical properties of the mosaic structure. If the heat treatment temperature is too low or too high, the improvement of the electrochemical performance of the composite material will be affected. Preferably, in step 2, the heat treatment temperature is 400-500°C.

[0016] Furthermore, in step 2, the inert gas is one or more of nitrogen, argon and helium.

[0017] Furthermore, in step 3, the heat-treated material is pickled until the washing liquid is colorless, and then dried.

[0018] Furthermore, one or more of acetic acid, hydrochloric acid, nitric acid and sulfuric acid are used for pickling, and the concentration of the acid is 0.1 to 2M.

[0019] Furthermore, in step 3, the drying is performed by vacuum drying or forced air drying, and the drying temperature is 60-120°C.

[0020] Furthermore, in the silicon-carbon composite material, the mass of the carbon layer accounts for 1% to 10% of the total mass of the silicon-carbon composite material.

[0021] In some embodiments, silicon particles coated with a carbon layer, that is, a silicon-carbon composite material, can be directly purchased or prepared during use.

[0022] In some embodiments, the silicon-carbon composite material is prepared by chemical vapor deposition.

[0023] Another object of the present invention is to protect the modified silicon-carbon composite material prepared by the above method.

[0024] The modified silicon-carbon composite material is prepared by the above-mentioned method for preparing the modified silicon-carbon composite material.

[0025] The present invention provides a modified silicon-carbon composite material, which has silicon particles as the core and an outer layer coated with a carbon-fluorine-embedded carbon layer structure with carbon fluoride defects. When used in lithium-ion batteries, after charging and discharging, the outer layer will form a structural layer of lithium fluoride particles and carbon embedding, which has excellent mechanical strength and rapid transmission capability of electrons and ions, and can significantly improve the electrochemical properties of silicon-carbon materials.

[0026] Another object of the present invention is to protect the application of the modified silicon-carbon composite material.

[0027] The modified silicon-carbon composite material mentioned above is used in the preparation of lithium-ion batteries.

[0028] The invention provides application of a modified silicon-carbon composite material in preparing a lithium ion battery, which has outstanding effects and is easy to promote.

[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0030] 1. The present invention provides a method for preparing a modified silicon-carbon composite material. The silicon-carbon composite material in which silicon particles are coated with a carbon layer is used as the basis for improvement. The mixture of the silicon-carbon composite material and a fluoride is subjected to heat treatment, pickling and drying under the protection of an inert gas to obtain a modified silicon-carbon composite material. The modified material forms a carbon-fluorine inlaid structure with fluorinated carbon defects on the outside of the silicon particles. The modified material is assembled into a lithium-ion battery. After charging and discharging, the carbon-fluorine bonds are broken and fluorine-lithium bonds are generated. The silicon particles are coated with lithium fluoride particles and a carbon-inlaid structural layer. The single-layer structure formed on the outside of the silicon particles can effectively improve the rapid transmission capability of electrons and ions, and has excellent mechanical strength, better fracture resistance during continuous charging and discharging, and further improved conductivity, so that the electrochemical performance of the lithium-ion battery is significantly improved. The preparation method is simple and easy to control.

[0031] 2. The present invention provides a modified silicon-carbon composite material, which has silicon particles as the core and an outer layer coated with a carbon-fluorine-embedded carbon layer structure with carbon fluoride defects. When used in lithium-ion batteries, after charging and discharging, the outer layer will form a structural layer of lithium fluoride particles and carbon embedding, which has excellent mechanical strength and rapid transmission capability of electrons and ions, and can significantly improve the electrochemical properties of silicon-carbon materials.

[0032] 3. The present invention provides an application of a modified silicon-carbon composite material in the preparation of lithium-ion batteries, which has outstanding effects and is easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the preparation and application principle of the modified silicon-carbon composite material of the present invention.

[0034] Figure 2 This is a transmission electron microscope image of carbon-coated micronized silicon.

[0035] Figure 3 This is the thermogravimetric data of carbon-coated silicon material.

[0036] Figure 4 Transmission electron microscopy image of the electrode after cycling.

[0037] Figure 5 AFM images of the electrode surfaces of the liquid batteries prepared with the materials of Example 1 and Comparative Example 1 after electrochemical cycles. DETAILED DESCRIPTION

[0038] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] The present invention aims to provide a modified silicon-carbon composite material, specifically a silicon-carbon composite material in which silicon particles are coated with a carbon layer as an improved basis, and a mixture of the silicon-carbon composite material and a fluoride is subjected to heat treatment, pickling and drying under the protection of an inert gas to obtain a modified silicon-carbon composite material, wherein the modified material forms a carbon-fluorine inlaid structure with fluorinated carbon defects on the outside of the silicon particles, and the modified material is assembled into a lithium-ion battery. After charging and discharging, the carbon-fluorine bonds are broken and the fluorine-lithium bonds are generated, and lithium fluoride particles and a carbon-inlaid structural layer are formed on the outside of the silicon particles. The single-layer structure formed on the outside of the silicon particles can effectively improve the rapid transmission capability of electrons and ions, and has excellent mechanical strength, better fracture resistance during continuous charging and discharging, and further improved conductivity, so that the electrochemical performance of the lithium-ion battery is significantly improved.

[0041] Specific as Figure 1 As shown, the silicon-carbon composite material and the modified silicon-carbon composite material of the present application, and the electrochemical enhancement principle diagram.

[0042] In some embodiments, silicon particles coated with a carbon layer, that is, a silicon-carbon composite material, can be directly purchased or prepared during use.

[0043] In some embodiments, the silicon-carbon composite material is prepared by chemical vapor deposition.

[0044] In some embodiments, the chemical vapor deposition method is specifically performed as follows:

[0045] Silicon particles are placed in a magnetic boat and placed in a tube furnace. Under the protection of inert gas, a carbon source is introduced into the high-temperature tube furnace at a certain rate and proportion at a certain heating rate and kept warm for a certain time. A carbon layer is coated on the surface of the silicon particles by chemical vapor deposition to obtain a silicon-carbon composite material.

[0046] In some embodiments, the particle size of the silicon particles is 30 nm, 100 nm, 500 nm, 1 μm or 5 μm, which can be adjusted according to actual application.

[0047] In some embodiments, the inert gas is one or more of nitrogen, argon, and helium; the carbon source is one or more of methane, acetylene, ethylene, and propylene.

[0048] In some embodiments, the heating rate is 2-10°C / min, which can be adjusted according to actual conditions. The gas flow rate is 80-120mL / min, which can be adjusted according to actual conditions; the volume ratio of the protective gas to the carbon source is 90-96:10-4; which can be adjusted according to actual conditions.

[0049] In some embodiments, the heating temperature of the tubular furnace is 800-1200° C.; the insulation time is 10 min-180 min; the carbon content of the obtained silicon-carbon composite material is 1-10 wt %, which can be adjusted according to actual conditions.

[0050] In the following examples and comparative examples, the silicon-carbon composite material was prepared by chemical vapor deposition, and the specific preparation method was as follows:

[0051] A raw material of silicon particles with a particle size of 500nm is placed in a magnetic boat and heated to 900°C in a tube furnace in an argon atmosphere at a heating rate of 5°C / min. Then the argon flow is reduced and methane is introduced. The ratio of argon to methane is 95:5, the total flow rate is 100s.ccm, and the ventilation time is 10min. The carbon content of the obtained silicon-carbon composite material is about 4wt%, and the structure is a carbon layer covering the surface of the silicon particles.

[0052] Figure 2 TEM images of carbon-coated silicon at different magnification scales show that the carbon is evenly and completely coated on the surface of micron silicon, and the coating thickness is about tens to hundreds of nanometers.

[0053] Figure 3 Thermogravimetric diagram of carbon-coated silicon. The carbon mass accounts for about 4% of the composite material.

[0054] Example 1

[0055] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0056] Step 1: Mix the silicon-carbon composite material and cobalt fluoride; the weight ratio of the silicon-carbon composite material to the fluoride is 3:1.

[0057] Step 2: Under the protection of inert gas nitrogen, the mixture obtained in step 1 is heat treated in a tube furnace; the heat treatment temperature is 450° C. and the heat treatment time is 6 hours.

[0058] Step 3: The material after the heat treatment in step 2 is pickled with 1M dilute hydrochloric acid until the washing liquid is colorless, and then dried to obtain a modified silicon-carbon composite material.

[0059] Example 2

[0060] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0061] Step 1: Mix the silicon-carbon composite material and sodium fluoride; the weight ratio of the silicon-carbon composite material to the fluoride is 2:1.

[0062] Step 2: Under the protection of inert gas (nitrogen, argon, helium), the mixture obtained in step 1 is heat treated in a tube furnace; the heat treatment temperature is 400° C. and the heat treatment time is 5 hours.

[0063] Step 3: pickle the material after the heat treatment in step 2 with 2M acetic acid until the washing liquid is colorless, and dry it to obtain a modified silicon-carbon composite material.

[0064] Example 3

[0065] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0066] Step 1: Mix the silicon-carbon composite material, cobalt fluoride and magnesium fluoride (the weight ratio of cobalt fluoride to magnesium fluoride is 1:1); the weight ratio of the silicon-carbon composite material to the fluoride is 4:1.

[0067] Step 2: Under the protection of inert gas (nitrogen, argon, helium), the mixture obtained in step 1 is heat treated in a tube furnace; the heat treatment temperature is 500° C. and the heat treatment time is 4 hours.

[0068] Step 3: The material after the heat treatment in step 2 is pickled with 0.1M sulfuric acid until the washing liquid is colorless, and then dried to obtain a modified silicon-carbon composite material.

[0069] Example 4

[0070] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0071] Step 1: Mix the silicon-carbon composite material and cobalt fluoride; the weight ratio of the silicon-carbon composite material to the fluoride is 1:1.

[0072] Step 2: Under the protection of inert gas (nitrogen, argon, helium), the mixture obtained in step 1 is heat treated in a tube furnace; the heat treatment temperature is 200° C. and the heat treatment time is 8 hours.

[0073] Step 3: The material after the heat treatment in step 2 is pickled with 1M nitric acid until the washing liquid is colorless, and then dried to obtain a modified silicon-carbon composite material.

[0074] Example 5

[0075] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0076] Step 1: Mix the silicon-carbon composite material and magnesium fluoride; the weight ratio of the silicon-carbon composite material to the fluoride is 5:1.

[0077] Step 2: Under the protection of inert gas nitrogen, the mixture obtained in step 1 is heat treated in a tube furnace; the heat treatment temperature is 600° C. and the heat treatment time is 2 h.

[0078] Step 3: The material after the heat treatment in step 2 is pickled with 1M dilute hydrochloric acid until the washing liquid is colorless, and then dried to obtain a modified silicon-carbon composite material.

[0079] Comparative Example 1

[0080] Comparative Example 1 only provides the same unmodified silicon-carbon composite material as Example 1.

[0081] Comparative Example 2

[0082] In the process of preparing the modified silicon-carbon composite material in Comparative Example 2, the pyrolysis temperature was adjusted compared with Example 1, and the other preparation processes and process parameters were the same as those in Example 1, as follows:

[0083] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0084] Step 1: Mix the silicon-carbon composite material and cobalt fluoride; the weight ratio of the silicon-carbon composite material to the fluoride is 3:1.

[0085] Step 2: Under the protection of inert gas nitrogen, the mixture obtained in step 1 is heat treated in a tube furnace; the heat treatment temperature is 150° C. and the heat treatment time is 6 hours.

[0086] Step 3: The material after the heat treatment in step 2 is pickled with 1M dilute hydrochloric acid until the washing liquid is colorless, and then dried to obtain a modified silicon-carbon composite material.

[0087] Comparative Example 3

[0088] In the process of preparing the modified silicon-carbon composite material in Comparative Example 3, the pyrolysis temperature was adjusted compared with Example 1, and the other preparation processes and process parameters were the same as those in Example 1, as follows:

[0089] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0090] Step 1: Mix the silicon-carbon composite material and cobalt fluoride; the weight ratio of the silicon-carbon composite material to the fluoride is 3:1.

[0091] Step 2: Under the protection of inert gas nitrogen, the mixture obtained in step 1 is heat treated in a tube furnace; the heat treatment temperature is 800° C. and the heat treatment time is 6 hours.

[0092] Step 3: The material after the heat treatment in step 2 is pickled with 1M dilute hydrochloric acid until the washing liquid is colorless, and then dried to obtain a modified silicon-carbon composite material.

[0093] Comparative Example 4

[0094] The modified silicon-carbon composite material provided in Comparative Example 4 is prepared by simply mixing the silicon-carbon composite material and the fluoride, and the specific operation is as follows:

[0095] A method for preparing a modified silicon-carbon composite material comprises the following steps:

[0096] Step 1: Mix the silicon-carbon composite material and cobalt fluoride; the weight ratio of the silicon-carbon composite material to the fluoride added is 3:1, to obtain a modified silicon-carbon composite material.

[0097] test

[0098] The materials prepared in Examples 1-5 and Comparative Examples 1-4 were prepared into liquid half-cells and solid-state batteries. The specific preparation process is as follows:

[0099] Liquid half-cell: The modified silicon-carbon composite materials prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-4 were respectively mixed with conductive agent carbon black and binder polyacrylic acid in a ratio of 8:1:1 to prepare a slurry, coated on copper foil, dried overnight at 80°C by blowing, and cut into circular pole pieces with a diameter of 12 mm. During the battery assembly process, a half-cell was assembled with a lithium sheet as the negative electrode and a silicon-carbon composite electrode as the positive electrode for long cycle and rate performance tests.

[0100] The liquid half-cell was tested with a voltage window of 0.02 to 1 V at a current density of 1 A g -1 Capacity retention after 400 cycles under the conditions of .

[0101] Test liquid half-cell, test voltage window is 0.02~1V, current density is 4A -1 The specific discharge capacity after 100 cycles at a current of is shown in Table 1.

[0102] Testing of solid-state battery full cell: The modified silicon-carbon composite materials prepared in Examples 1-5 and the materials prepared in Comparative Examples 1-4 were used as negative electrodes, NCM811 as positive electrodes, and solid-state full cells were assembled using PVDF-based solid electrolytes.

[0103] The test current density is 0.5C (1C = 200mA g -1 ), the capacity retention rate after 400 cycles and the discharge specific capacity after 100 cycles under the condition of current density of 1C were counted. The specific test results are shown in Table 1.

[0104] Table 1

[0105]

[0106] It can be seen from the test results in Table 1 that the electrochemical properties of the modified silicon-carbon composite material prepared in the present application are significantly improved compared with the electrochemical properties of the pure silicon-carbon composite material. The addition ratio of the silicon-carbon composite material and the fluoride and the heat treatment temperature have a certain influence on the improvement effect. The electrochemical materials prepared using the designed raw materials of the present invention have improved performance, and the required battery performance can be specifically adjusted by the addition ratio and the heat treatment temperature.

[0107] After the modified silicon-carbon composite material prepared in the present application is prepared into a lithium-ion battery, after charging and discharging, a structural layer of lithium fluoride particles and carbon inlays will be formed on the outer layer, which has excellent mechanical strength and rapid transmission capability of electrons and ions, and can significantly improve the electrochemical performance of silicon-carbon materials.

[0108] like Figure 4 As shown, the modified silicon-carbon composite material prepared in Example 1, after the electrode cycle, can be seen from the transmission electron microscope that the embedded structure of lithium fluoride and carbon layer.

[0109] Figure 5 Atomic force microscopy tests were performed on the electrode surfaces of the materials prepared in Example 1 and Comparative Example 1 after 10 cycles. From the test results, it can be seen that the electrode surface of the modified silicon-carbon composite material of the present invention is smoother after the cycle, indicating that the electrode structure is more stable.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified silicon-carbon composite material, characterized in that: The following steps are involved: Step 1, mixing the silicon-carbon composite material and the fluoride; Step 2: heat-treating the mixture obtained in step 1 in a tube furnace under the protection of inert gas; Step 3, pickling and drying the material after the heat treatment in step 2 to obtain a modified silicon-carbon composite material; The structure of the silicon-carbon composite material is that the surface of silicon particles is coated with a carbon layer.

2. The method for preparing the modified silicon-carbon composite material according to claim 1, characterized in that: The fluoride is at least one of sodium fluoride, cobalt fluoride and magnesium fluoride.

3. The method for preparing the modified silicon-carbon composite material according to claim 1, characterized in that: In step 1, the weight ratio of the silicon-carbon composite material to the fluoride is 1 to 5:

1.

4. The method for preparing the modified silicon-carbon composite material according to claim 1, characterized in that: In step 2, the heat treatment temperature is 200 to 600° C.; and / or the heat treatment time is 2 to 8 hours.

5. The method for preparing the modified silicon-carbon composite material according to claim 4, characterized in that: In step 2, the temperature of the heat treatment is 400-500°C.

6. The method for preparing the modified silicon-carbon composite material according to claim 1, characterized in that: In step 3, the heat-treated material is pickled until the washing liquid is colorless and then dried.

7. The method for preparing the modified silicon-carbon composite material according to any one of claims 1 to 6, characterized in that: In the silicon-carbon composite material, the mass of the carbon layer accounts for 1% to 10% of the total mass of the silicon-carbon composite material.

8. The method for preparing the modified silicon-carbon composite material according to claim 7, characterized in that: The silicon-carbon composite material is prepared by chemical vapor deposition.

9. A modified silicon-carbon composite material prepared by the method for preparing a modified silicon-carbon composite material according to any one of claims 1 to 8.

10. Use of the modified silicon-carbon composite material as claimed in claim 9 in the preparation of lithium-ion batteries.

Citation Information

Patent Citations

  • Surface-modified silicon-carbon composite material and preparation method and application thereof

    CN109546122A

  • Silicon-based lithium storage material and preparation method thereof

    CN112219295A

  • Composite negative electrode material and preparation method and application thereof

    CN115000392A

  • Preparation method and application of silicon fluoride carbon negative electrode material

    CN115799474A

  • Fluorine layer coating, carbon layer coating, and negative electrode active material

    JP2019021451A

Cited By

  • Silicon-based negative electrode material and preparation method and application thereof

    CN120097346A